Response of Pathogenic Vibrio Species to High Hydrostatic Pressure - Berlin, Daniel L. (American Society for Microbiology, 1999)
Vibrio parahaemolyticus ATCC 17802, Vibrio vulnificus ATCC 27562, Vibrio cholerae O:1 ATCC 14035, Vibrio cholerae non-O:1 ATCC 14547, Vibrio hollisae ATCC 33564, and Vibrio mimicus ATCC 33653 were treated with 200 to 300 MPa for 5 to 15 min at 25°C. High hydrostatic pressure inactivated all strains of pathogenic Vibrio without triggering a viable but nonculturable (VBNC) state; however, cells already existing in a VBNC state appeared to possess greater pressure resistance.